PELAKSANAAN PEMANFAATAN PERPUSTAKAAN DI SLB NEGERI MANGGIS GANTING BUKITTINGGI - Rizki - Febrianda (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by library in SLB Negeri Manggis Ganting Bukittinggi that still need to be perfected, where not all library requirements are met. The purpose of this research is to look deeper into how the implementation of the use of the library in SLB Manggis Ganting Bukittinggi in organizing the library that  can  be  the  best.   This  research  use  descriptive  method  with  qualitative approach.  Techniques  used  in  collecting  data  are  observation,  interview  and documentary, while data sources are library employee, manager the school budget, the head of the institution (the principal).  Results showed implementation in the library of SLB Negeri Manggis Ganting Bukittinggi still qualify are still not meet the standards. In accordance with the above results it is  recommended that the existing schools to pay more attention to activities of the library, by giving budgets and policies that can support library services and further improve the  quality of service, especially students have a high interest in reading.